Impact of wildfires on SO2 detoxification mechanisms in leaves of oak and beech trees. (1st March 2021) - Weber, Jan-Niklas; Kaufholdt, David; Minner-Meinen, Rieke; Bloem, Elke; Shahid, Afsheen; Rennenberg, Heinz; Hänsch, Robert
Abstract: Frequency and intensity of wildfire occurrences are dramatically increasing worldwide due to global climate change, having a devastating effect on the entire ecosystem including plants. Moreover, distribution of fire-smoke can influence the natural environment over very long distances, i.e. hundreds of kilometres. Dry plant matter contains 0.1–0.9% (w/w) sulphur, which is mainly released during combustion into the atmosphere as sulphur dioxide (SO2 ) resulting in local concentrations of up to 3000 nL L −1 . SO2 is a highly hazardous gas, which enters plants mostly via the stomata. Toxic sulphite is formed inside the leaves due to conversion of SO2 . Plants as sessile organisms cannot escape from threats, why they evolved an impressive diversity of molecular defence mechanisms. In the present study, two recent wildfires in Germany were evaluated to analyse the effect of SO2 released into the atmosphere on deciduous trees: the Meppen peat fire in 2018 and the forest fire close to Luebtheen in 2019. Collected leaf material from beech ( Fagus sylvatica ) and oak ( Quercus robur ) was examined with respect to detoxification of sulphur surplus due to the exposure to elevated SO2 . An induced stress reaction in both species was indicated by a 1.5-fold increase in oxidized glutathione. In beech leaves, the enzymatic activities of the sulphite detoxification enzymes sulphite oxidase and apoplastic peroxidases were increased 5-fold and a trend of sulphate accumulation was observed. In contrast, oaks did not regulate these enzymes during smoke exposure, however, the constitutive activity is 10-fold and 3-fold higher than in beech. These results show for the first time sulphite detoxification strategies of trees in situ after natural smoke exposure. Beech and oak trees survived short-term SO2 fumigation due to exclusion of toxic gases and different oxidative detoxification strategies. Beeches use efficient upregulation of oxidative sulphite detoxification enzymes, while oaks hold a constitutively high enzyme-pool available. Graphical abstract: Image 1 Highlights: Global climate change results in an increase in frequency and intensity of wildfires. SO2 harms plants after entering leaves and converting into toxic sulphite. Beech and oak leaves exposed to smoke of wildfires in Germany were investigated. Trees survive short-term smoke exposure primary by oxidative detoxification strategy. Oak constitutively oversupplies enzyme activities whereas beech upregulates upon need.